ANALISIS PENGARUH KONSENTRASI EKOENZIM TERHADAP KUALITAS AIR BERDASARKAN PARAMETER FISIKA : AROMA, pH, KEKERUHAN, DAN KONDUKTIVITAS AIR YANG TERCEMAR - Bissilisin, Nikson (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
The general objective of this study is to analyze the effect of ecoenzyme concentration on contaminated water quality parameters. The specific objectives of this study are to determine the effect of ecoenzymes on physical indicators of water, such as the odor of contaminated water, the pH of contaminated water, the turbidity of contaminated water, and the conductivity of contaminated water. The research method used in this study is a True Experiment and a Completely Randomized Design. The results of the study indicate that the effect of ecoenzymes on the characteristics of contaminated wastewater is very good because there are supporting enzymes that help clarify contaminated wastewater. Additionally, the application of ecoenzymes to contaminated water, particularly to address odor, is very effective because the enzymes in ecoenzymes help eliminate odor-producing bacteria in contaminated wastewater. The use of ecoenzymes has a significant impact on conductivity values.